Seismic structure of the Central Tyrrhenian basin: Geophysical constraints on the nature of the main crustal domains. Issue 1 (13th January 2014) - Prada, M.; Sallares, V.; Ranero, C. R.; Vendrell, M. G.; Grevemeyer, I.; Zitellini, N.; de, R.
Abstract [1] In this work we investigate the crustal and tectonic structures of the Central Tyrrhenian back‐arc basin combining refraction and wide‐angle reflection seismic (WAS), gravity, and multichannel seismic (MCS) reflection data, acquired during the MEDOC (MEDiterráneo OCcidental)‐2010 survey along a transect crossing the entire basin from Sardinia to Campania at 40°N. The results presented include a ~450 km long 2‐D P wave velocity model, obtained by the traveltime inversion of the WAS data, a coincident density model, and a MCS poststack time‐migrated profile. We interpret three basement domains with different petrological affinity along the transect based on the comparison of velocity and velocity‐derived density models with existing compilations for continental crust, oceanic crust, and exhumed mantle. The first domain includes the continental crust of Sardinia and the conjugate Campania margin. In the Sardinia margin, extension has thinned the crust from ~20 km under the coastline to ~13 km ~60 km seaward. Similarly, the Campania margin is also affected by strong extensional deformation. The second domain, under the Cornaglia Terrace and its conjugate Campania Terrace, appears to be oceanic in nature. However, it shows differences with respect to the reference Atlantic oceanic crust and agrees with that generated in back‐arc oceanic settings. The velocities‐depth relationships and lack of Moho reflections in seismic records of the third domain (i.e., the Magnaghi and Vavilov basins) support a basement fundamentally made of mantle rocks. The large seamounts of the third domain (e.g., Vavilov) are underlain by 10–20 km wide, relatively low‐velocity anomalies interpreted as magmatic bodies locally intruding the mantle.